THE IMPLEMENTATION OF ANALYSIS ZAKAT ACCOUNTING STANDARDS AND ACCOUNTABILITY OF FINANCIAL REPORTS - Hastuti Olivia; Ahmad Qorib; Nurlaila Nurlaila (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze how the application of accounting applied by the Baitul Maal Hidayatullah Amil Zakat institution and whether it is in accordance with PSAK No.109 on Zakat Accounting, besides the purpose of this study is to analyze the accountability of financial statements that exist in the Amil Zakat Institution Baitul Maal Hidayatullah the data used are primary data taken by interview method and using secondary data with the study of documentation and study of financial statement records in completing this research reference. The results of the study concluded that the financial statements implemented by the amil zakat Baitul Maal Hidayatullah institution are still in the form of Cash Flow and Balance Sheet Reports, Baitul Maal Hidayatullah acually has applied PSAK No.109. while the application of accountability carried out by amil zakat Baitul Maal Hidayatullah institutions in the presentation of financial statements and moral and spiritual reporting has been carried out well, but the physical aspects of accountability have not been fully carried out in accordance with PSAK No.109 concerning Accounting for Zakat, Infaq/Alms. Keywords: Zakat, PSAK No.109, Accountability